2008
DOI: 10.2165/00044011-200828020-00006
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic-Pharmacodynamic Relationship of Dobutamine and Heart Rate, Stroke Volume and Cardiac Output in Healthy Volunteers

Abstract: Low plasma concentrations of dobutamine resulted in an increase in CO almost solely due to improved left ventricular contractility. However, at higher plasma concentrations of dobutamine, SV remained stable or even decreased, and the linear increase in CO was entirely based on increased HR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 14 publications
4
9
0
Order By: Relevance
“…The peripheral vasodilation, indicated by a decrease in SVR, combined with an increase in CO and SV positively influenced local blood flow in this experiment. Previous studies in anaesthetised horses , cats and man using comparable doses, showed similar results regarding systemic haemodynamic parameters. In terms of altering local mesenterial blood flow or oxygen delivery, previous studies in hypotensive foals or experimental models of sepsis failed to show a significant influence on the gastrointestinal perfusion, although jejunal mucosal blood flow has been shown to improve after cardiac surgery with dobutamine infused at 2.7 ± 0.1 μg/kg bwt/min .…”
Section: Discussionsupporting
confidence: 72%
“…The peripheral vasodilation, indicated by a decrease in SVR, combined with an increase in CO and SV positively influenced local blood flow in this experiment. Previous studies in anaesthetised horses , cats and man using comparable doses, showed similar results regarding systemic haemodynamic parameters. In terms of altering local mesenterial blood flow or oxygen delivery, previous studies in hypotensive foals or experimental models of sepsis failed to show a significant influence on the gastrointestinal perfusion, although jejunal mucosal blood flow has been shown to improve after cardiac surgery with dobutamine infused at 2.7 ± 0.1 μg/kg bwt/min .…”
Section: Discussionsupporting
confidence: 72%
“…For both temperature conditions, dobutamine resulted in elevated HR consistent with previous findings [27,28]. The hypothermic condition resulted in a slightly larger increase in HR of 29% compared to an increase of 23% in the hyperthermic condition, likely due to an increase in baseline heart rate at 38 °C [19,29].…”
Section: Discussionsupporting
confidence: 88%
“…In healthy volunteers, increasing the dose of dobutamine results in elevated cardiac output, which is linearly related to its plasma concentrations. ( 13 ) The relationships between heart rate and stroke volume to plasma concentrations, however, are more complex. Heart rate initially remains unchanged and then increases with higher concentrations, while stroke volume only increases at lower concentrations.…”
Section: Effects Of Dobutamine In Normal Subjectsmentioning
confidence: 99%
“…In these circumstances, the augmentation in cardiac output goes together with elevations in blood pressure. ( 11 - 13 )…”
Section: Effects Of Dobutamine In Cardiac Failurementioning
confidence: 99%